Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T19:43:18+01:00
29.
2x-2y= 10
x+2y=20

3x=30 /3
x=10

10+2y=20
2y=20-10
2y=10 /:2

y=5
x=10

30.
x+4y= 37 / *(-2)
2x+5y= 53

-2x-4y= -74
2x+5y=53

y= -21
x+4*(-21)=37
x-84=37

x=121
y=-21

31.
m+2n=31
2n-m=29

m+2n=31
-m+2n=29

4n=60 /:4
n=15

m+2*15=31
m+30=31

m=1
n=15

32.
5p-q=21
q-2p=-9

5p-q=21
-2p+q=-9

3p=12 /:3
p=4

5*4-q=21
20-q=21
-q=1

q=-1
p=4

33.
5u-v=72 / *(-1)
3u-v=44

-5u+v=-72
3u-v=44

-2u=-28 /:(-2)
u=14

3*14-v=44
42-v=44
-v=2 /:(-1)

v=-2
u=14

34.
5x-2y=26
9x+y=33 /*2

5x-2y=26
18x+2y=66

23x=92 /:23
x=4

5*4-2y=26
20-2y=26
-2y=6 /(-2)

y=-3
x=4



2010-02-09T19:51:00+01:00
<29>
2x-2y=10
X+2y=20

x=20-2y
2(20-2y)-2y=10

x=20-2y
40-4y-2y=10

X=20-2y
-6y=-30 /:-6

X=20-2y
Y=5

X=20-10=10
Y=5

<30>
x+4y=37
2x+5y=53

X=37-4y
2(37-4y)+5y=53

X=37-4y
74-8y+5y=53

X=37-4y
-3y=53-74=-21 /:-3

X=37-4y
Y= 7

X=37-28=9
Y=7

<31>
m+2n=31
2m-n=29

M=31-2n
2(31-2n)-n=29

M=31-2n
62-4n-n=29

M=31-2n
-5n=29-62= -33 /:-5

M=31-2n
n=6 3/5

<32>

5p-q=21
q-2p=-9

q=-9+2p
5p+9-2p=21

q=-9+2p
3p=12 /:3

q=-9+2p
p=4

q=-9+8=-1
p=4

narazie nie mam czasu robic wiecej ... ;/
2010-02-09T20:07:11+01:00
58) 8-y=11x
y=7x-1

podstawiamy drugie równanie do pierwszego
ale najpierw uporządkujemy dane

-y-11x=-8
-7x+1-11x=-8
-18x=-9
x=1/2 czyli 0,5
y=7*0,5-1
y=2,5

57)
9y+3=16-8x
x+y=1 -> x=1-y

9y+3=16-8(1-y)
9y+3=16-8+8y
9y-8y=8-3
y=5

x=1-y
x=1-5
x=-4

56)
x+3y=8x-8y
7x-13=12y-20

x-8x+3y+8y=0
7x-12y=-20+13

-7x+11y=0-> -7x=-11y -> x=11/7y
7x-12y=-7

7*11/7y-12y=-7
11y-12y=-7
-y=-7
y=7

x=11/7*7
x=11

55)
3x+2y+9=0
2x+3y+1=0

3x+2y=-9
2x+3y=-1 -> 2x=-1-3y -> x= (1-3y)/2

3*(1-3y)/2+2y=-9
(3-9y)/2+2y=-9
3/2 -9/2y+2y=-9/*2
3-9y+4y=-18
-5y=-21
y=4 i 1/5
x=(1-3*21/5)/2
x=(1-63/5)/2
x=-58/5*1/2
x=-29/5
x=-5 i 4/5

54)
3x+7y=-8/*(-5)
5x-6y=-31/*3

-15x-35y=40
15x-18y=-93
podsumujmy
0x-53y=-53
y=1

3x+7=-8
3x=-8-7
3x=-15

53)
5x+4y=-18/(-2)
2x+3y=-10/*5

-10x-8y=36
10x+15y=-50
sumujemy
7y=-14
y=-2

2x-6=-10
2x=-4
x=-2

1)
2x+y=5
x=3
6+y=5
y=5-6
y=-1

2)
x-y=2
x=-1

-1-y=2
-y=3
y=-3

3)
3x+2y=3
y=1

3x+2=3
3x=1
x=1/3

4)
2x+y=2
y=0

2x=2
x=1

5)
-2x+3y=0
x=3

-6+3y=0
3y=6
y=2

6)
3x-2y=4
y=1

3x-2=4
3x=6
x=2

7)
3x+y=10
y=2x

3x+2x=10
5x=10/5
x=2

y=4

8)
x+2y=14
y=3x

x+6x=14
7x=14
x=2
y=6